Toward an understanding of the flood traumatic stress disorder (FTSD) from an Islamic perspective: a conceptual introduction - Hj. Yaakub, Muhamadul Bakir; Othman, Khatijah (Perkama Consultants Sdn. Bhd., 2015)

(untitled)
This study traces the Islamic views that led to developing the Islamic perspectives of the diagnostically concept of flood traumatic stress disorder (FTSD). Examples of the catastrophic precipitants of FTSD, such as sleepless, frightened, helpless, forbear, and so on. As we know that highly stressful events can have profoundly negative psychological effects on the persons who experience them. Such effects can include confusion, anger, anxiety, feelings of helplessness, and depression (McCann & Perlman, 1990; Rubonis & Bickman, 1991). The flood that affected many areas in Malaysia in December 2014 had devastating effects on those who were directly and indirectly involved. The dispatch of material help was rather quickly and observable. However, there is doubt in term of the effectiveness of psychological interventions to understand the situation of the flood victims, especially from an Islamic perspective. Therefore, this study is trying to describe the emotional dimension of the flood victims within the description of Islamic fundamental resources and application. As a Muslim, it is something part, and parcel of his standard of leaving practices that require him to understand every single phenomenon or issue as according to the conceptual framework of Quranic principles and guidelines. For that reason, the Islamic academic culture of Muslim practices should conceive of “mind”, “body” and “soul”. These three elements should be developed and tied together in a comprehensive manner to achieve identical finding and understanding of human issues and problems. From this conceptual assumption, a study on the flooding impact supposed not to restrict only on physical casualties using a qualitative approach. In fact, it should also cover socio-cultural behaviours, religious educational understanding, and personal conduct, especially in term of achieving and maintaining psychological stability. In line with this perception, an essential postulate guiding this study is to analyze Islamic resources in describing a human being as a vicegerent of God on the earth facing traumatic tribulation in life. It is an exploration to uncover the importance role of Islamic religious education in shaping the characteristics and features of a traumatic personality. For example, much of post-flood traumatic stress disorder is distinctly human in nature. The standard approaches to understanding the situation of this type of human psychology based on human observational methods. Pargament (1990) also have similar assumptions. According to him, religious beliefs system can serve a useful function in human life, especially in allowing the individual to cope with traumatic events. In fact, we also found reports on public opinion polls in which it indicated that religion is considered an important part of the lives of many communities in the world. Therefore, understanding the role of religious beliefs is crucial in the coping process for FTSD (Princeton Religious Research Centre, 1988).